Strategi Pemanfaatan Media Sosial dalam Revitalisasi dan Promosi Pelestarian Seni Tembang Macapat (Studi Kasus pada Konten Kreator Bambang Sulanjari) - Awaludin, Muhammad Rizaol (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2025)
In this era of globalization we are required to master various technological tools. Not only that, we must also be able to take advantage of the sophistication of the impact of globalization. This study will examine how the use of social media in preserving Indonesian culture, one of which is the macapat song. The results of this study are in the form of ways so that macapat songs can still exist among teenagers by taking advantage of the progress of globalization through social media.